Sex-Specific Relationship Between Parathyroid Hormone and Platelet Indices in Phenotypes of Heart Failure—Results From the MyoVasc Study - Dahlen, Bianca; Müller, Felix; Tröbs, Sven-Oliver; Heidorn, Marc William; Schulz, Andreas; Arnold, Natalie; Hermanns, M. Iris; Schwuchow-Thonke, Sören; Prochaska, Jürgen H.; Gori, Tommaso; ten Cate, Hugo; Lackner, Karl J.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Heart failure (HF) is a multifactorial syndrome with pathophysiological complexities still not fully understood. Higher mean platelet volume (MPV), a potential marker of platelet activation, and high concentrations of parathyroid hormone (PTH) have been implicated in the pathogenesis of HF. Aim: This study aims to investigate sex-specifically the association between PTH concentrations and platelet indices in phenotypes of HF. Methods and Results: PTH and platelet indices (MPV and platelet count) were available in 1,896 participants from the MyoVasc study in Mainz, Germany. Multivariable linear regression models, adjusted for age, sex, season, vitamin D status, cardiovascular risk factors, comorbidities, estimated glomerular filtration rate, and medication, were used to assess the associations between platelet indices and PTH. The results showed distinct sex-specific associations between PTH and platelet indices. A positive association between PTH and MPV was found in females with symptomatic HF with reduced ejection fraction (HFrEF) only [β = 0.60 (0.19; 1.00)]. Platelet count was inversely associated with PTH in male HFrEF individuals [β = −7.6 (−15; −0.30)] and in both males and females with HF with preserved ejection fraction (HFpEF). Conclusion: This study reports differential, sex-specific relationships between PTH and platelet indices in HF individuals independent of vitamin D status and clinical profile. Particularly in phenotypes of symptomatic HF, distinct associations were observed, suggesting a sex-specific mechanism involved in the interaction between PTH and platelets.